The main foundation for educators in carrying out the learning process - Elihami, Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2021)
The principles of learning are the main foundation for educators in carrying out the learning process. With these principles in place, the learning process in the classroom, both educators and students, will forgive all elements of learning. The principles of learning in general are attention and motivation, activeness, direct involvement, repetition, challenges and individual differences. Attention and motivation is Motivation is the energy that moves and directs one’s activities. Motivation has a close relationship with interest. Students who have an interest in a particular field of study tend to be attracted to it and thus the motivation to study it arises. With motivation, it will provide a stimulus to students for motivation in participating in learning. Activeness is the seriousness of students in discussing the subject matter that has been discussed. Direct involvement is an active student effort in the learning process. Repetition is giving students the opportunity to review material again so that students understand the material that has been presented. The challenge is to provide a variety of materials that are difficult for students to solve. Individual differences are differences between students from each other